Dutch runners: Serving the running market through technology - de Gruijter, M. (New Studies in Athletics, 2013)
ABSTRACT Within the running market in the Netherlands there are two distinct groups: those who run individually and those who run in groups. Running as part of a group is facilitated by various clubs and running groups. To improve its position in the market and establish itself as the natural authority for running in the mind of the public, the Royal Dutch Athletics Federation has developed the Dutch Runners programme for individuals not interested in affiliating with a club or running group. The programme includes a direct membership scheme and technological developments such as an online platform, an audio coaching tool and a smart phone application, which together create chances to respond to the needs of individual runners and thereby support greater participation in the sport. This case study describes the elements of the programme and results through 2013. The author's conclusions are 1) the initiative has helped to increase membership and contributed to the national trend of more people exercising regularly and 2) the elements of the programme can be transferred to other European countries for the benefit of runners and national athletics federations.